Social Competence Intervention for Parents (SCI-P): Comparing Outcomes for a Parent Education Program Targeting Adolescents with ASD. (18th April 2012) - Schultz, Tia R.; Stichter, Janine P.; Herzog, Melissa J.; McGhee, Stephanie D.; Lierheimer, Kristin
Abstract : Research has shown that parent education programs can address some of the distinct challenges that parents of youth with autism spectrum disorders (ASDs) encounter. This study examined the effectiveness of the Social Competence Intervention for Parents (SCI-P), a parent education program, administered in conjunction with a social competence intervention that targeted youth with ASD ages 11–14 (SCI-A). Using a quasi-experimental pre-post design, parents were assigned to either the SCI-P group (n = 16 ) or to the waitlist comparison group (n = 10 ). Analyses of covariance (ANCOVAs) revealed a significant effect for parent education participation such that SCI-P participants experienced significantly greater reductions in levels of stress and a trend for increases in parenting sense of competence from pre- to post-intervention. Moreover, parents in the SCI-P group reported high satisfaction with the program. These findings suggest that parent education can result in positive outcomes for parents' well being.